(untitled) (Papeles, 2011)
This article contains some reflection of the research results and Heritage Cultural Industry Social (2010) which sought to look at the relationship of these two concepts in their play of interests in the contemporary context framework and take the pulse of the various guilds and sectors of cultural production in recent years, starting from the question of how to make the Corporate Social Responsibility and the influence of this current on setting the conditions under which it occurs and is protected culture in Colombia.